2014
DOI: 10.1002/adma.201400087
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Conversion of CO2 into Renewable Hydrocarbon Fuels: State‐of‐the‐Art Accomplishment, Challenges, and Prospects

Abstract: Photocatalytic reduction of CO2 into hydrocarbon fuels, an artificial photosynthesis, is based on the simulation of natural photosynthesis in green plants, whereby O2 and carbohydrates are produced from H2 O and CO2 using sunlight as an energy source. It couples the reductive half-reaction of CO2 fixation with a matched oxidative half-reaction such as water oxidation, to achieve a carbon neutral cycle, which is like killing two birds with one stone in terms of saving the environment and supplying future energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
880
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,411 publications
(926 citation statements)
references
References 266 publications
(412 reference statements)
10
880
2
9
Order By: Relevance
“…Several reviews related to Z‐scheme water splitting have been reported,4, 8, 12 and all‐solid‐state Z‐scheme photocatalytic systems without redox pair were especially summarized, which mainly exhibit the obvious differences of all‐solid‐state Z‐scheme systems in the preparation methodology, working mechanism, properties and application 7. Some Z‐scheme examples were also partly presented in our previous reviews about heterostructured photocatalysts3 and CO 2 photoreduction 15…”
Section: Introductionmentioning
confidence: 98%
“…Several reviews related to Z‐scheme water splitting have been reported,4, 8, 12 and all‐solid‐state Z‐scheme photocatalytic systems without redox pair were especially summarized, which mainly exhibit the obvious differences of all‐solid‐state Z‐scheme systems in the preparation methodology, working mechanism, properties and application 7. Some Z‐scheme examples were also partly presented in our previous reviews about heterostructured photocatalysts3 and CO 2 photoreduction 15…”
Section: Introductionmentioning
confidence: 98%
“…Several previous high‐quality review articles on similar topics are available 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26. Given the recent heightened research activities and increasingly deepened understanding of these two processes, we believe that an up‐to‐date account on their status and existing challenges is necessary so as to provide readers with a current snapshot of this rapidly evolving area.…”
Section: Introductionmentioning
confidence: 99%
“…CO, CH 4 ) which is generally less than tens of μmol per hour of illumination per gram of photocatalyst. 11,12 In artificial photosynthesis, the semiconductor should have appropriate conduction band minimum for the reduction half-reaction and valence band maximum for the oxidation half-reaction. Therefore, the main components of the common photocatalysts for CO 2 36,37 are quite difficult to promote the oxidation half-reaction, which leads to the generation of oxygen through the oxidation of water.…”
Section: Introductionmentioning
confidence: 99%